OVERVIEW OF FOOD CONSUMPTION BEHAVIOR AND HEALTHY LIFESTYLE PATTERNS IN MODERN COMMUNITIES OF BOGOR CITY - Septiana, Henni Rizki; Julianti, Revalina; Putri, Lyra Revaliana; Dinina, Ragil Choirunnisa Aufa; Azzahra, Saskia Devina; Gunawan, Sefhia Dwi Purwati (HEARTY, 2024)
The increasing level and lifestyle of society accompanied by the modernization of food industry technology has caused people to move away from natural foods and prefer fast food. Fast food is considered very practical, fast and easy to obtain so that it supports the lifestyle of modern society. This study aims to determine the description of food consumption behavior and healthy lifestyles in modern society in Bogor city. The method used was descriptive quantitative approach with data collection through interviews with questionnaires, the number of respondents was 200 people. Related to food consumption behavior, the results showed that most respondents, 62%, often consume fast food because it is practical and easy to obtain, 73.5% consume vegetables and fruit regularly and as many as 67.5% drink 8 glasses of water a day. Regarding a healthy lifestyle, 51% of respondents exercise regularly, 74% cook their own food, 76.5% rarely read labels when buying packaged food products, 54% have sufficient knowledge to distinguish healthy and unhealthy foods, 86% of respondents agree to pay attention to nutritional intake in daily consumption, and 76.5% rarely search for information related to healthy food. Despite exercising regularly and regularly consuming vegetables and fruits, frequent consumption of fast food can cause nutrition and health problems in the future. Self-education related to healthy food accompanied by concrete actions in daily food choices is needed to maintain health and quality of life.